2019
DOI: 10.5194/aab-62-9-2019
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of candidate genes associated with fattening performance in Holstein–Friesian bulls

Abstract: The objective of this study was to determine the association of single nucleotide polymorphisms (SNPs) in selected candidate genes with fattening performance traits in a commercial cattle herd. Fifteen SNPs in 12 candidate genes (LEP, FABP4, DGAT1, TG, IGF1, IGF1R, MYF5, LGB, CAPN1, CAST, GHR, and OLR1) were evaluated in 296 purebred Holstein–Friesian bulls using PCR-RFLP (polymerase chain reaction – restriction fragment length polymorphism). Associations between each segregating SNP and genetic merit for fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 74 publications
1
29
0
2
Order By: Relevance
“…Biological features of the young organism are rapid growth and lower consumption of nutrients per unit of increase in live weight [9][10]. With age, the efficiency of the use of nitrogen and energy expectedly decreases but remains 1.5-2 times higher than not only in extensive, semi-intensive, or intensive growing, but also at a more mature age.…”
Section: Resultsmentioning
confidence: 99%
“…Biological features of the young organism are rapid growth and lower consumption of nutrients per unit of increase in live weight [9][10]. With age, the efficiency of the use of nitrogen and energy expectedly decreases but remains 1.5-2 times higher than not only in extensive, semi-intensive, or intensive growing, but also at a more mature age.…”
Section: Resultsmentioning
confidence: 99%
“…A SNP located in intron 1 of the FABP4 (g.2834C>G) was associated with desirable increases in live weight, hot carcass weight, and chilled carcass weight. 2 On the other hand, in Holstein bulls, a potential novel effect of FABP4 gene polymorphisms on average daily weight gain was shown by Ardicli et al 9 This gene was associated with carcass weight in various commercial beef cattle populations. Mizoshita et al 22 demonstrated that a quantitative trait loci (QTL) for carcass weight in purebred Japanese Black (Waygu) is close to the FABP4 gene on BTA14.…”
Section: Discussionmentioning
confidence: 97%
“…6 Taken together, this gene has been suggested as a functional and positional candidate gene for the evaluation of fat synthesis dynamics in cattle. [7][8][9] Although FABP4 gene shows its main effects on meat quality, 5,10 it is also of great importance in terms of some carcass characteristics. 2,11,12 The c.328 G>A polymorphism (rs110652478) in the bovine FABP4 gene is located on exon 3 and it induces valine to methionine substitution at position 110.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leptin gene and its polymorphism have been studied in connection with energy metabolism in beef cattle, milk production [8][9][10][11][12] and fattening qualities [13] in Holstein animals. Chinese researchers were able to establish that a number of LEP polymorphisms are associated with body weight, heart girth, average daily gain, and body length in native Chinese cattle [14].…”
Section: Introductionmentioning
confidence: 99%